EFFECTS OF THE SEED OF Phalaris canariensis AND THE CHANGE OF DIET ON SERUM LIPIDS IN RATS - Ojeda, Luis; Ruiz, Yuliana Da; Martínez, Franklin; Odreman, Rafael; Torri, Juan; Villegas, Rodrigo; Ybarra, Luis Pérez; Machado, Nirza Noguera (Emirates Journal of Food and Agriculture, 2021)
Canary seed is a grassy plant in the family of poaceae, which grains are used almost exclusively to feed birds. With limited information reported but proven bioactive potential, led to study how does the consumption of a canary seed infusion affected rats with a change in a diet on the lipid profile, in an experimental model. The animals were divided into two groups, the first group received a hypercaloric diet (60 days) and the second was maintained on a normocaloric diet. Afterwards the groups were subdivided, one group received a diet change from hypercaloric to normocaloric, the second continued to receive the hypercaloric diet and the third kept a normocaloric diet, half of each group ingested 25% Canary seed infusion and the rest water for 45 days. Triglycerides, total cholesterol, HDL-c and LDL-c were determined. Results showed a statistically significant reduction of 30.08% in triglyceride values in the group with combination of Canary seed infusion with a dietary change, while in cholesterol metabolism there were no significant changes. Thus, the ability of canary seed infusion to reduce serum triglycerides when combined with a dietary change was confirmed.